2019
DOI: 10.1161/circulationaha.118.037231
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Stroke in the Long-Term Cohort of the MOMENTUM 3 Study

Abstract: Background: The MOMENTUM 3 study (Multicenter Study of MagLev Technology in Patients Undergoing Mechanical Circulatory Support Therapy With HeartMate 3) has demonstrated that the HeartMate 3 (HM3) pump is associated with reduced strokes compared with the HeartMate II (HMII) device. We now perform a comprehensive analysis of stroke events to evaluate their longitudinal occurrence, clinical correlates, patterns, and impact on outcome across the 2-year duration of support. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 25 publications
9
98
0
Order By: Relevance
“…This study shows safety and efficacy of an aspirin‐free antithrombotic regimen in reducing HRAEs in patients implanted with the HM3, and further expands the results by Lim et al , suggesting the potential benefit of primary warfarin monotherapy after discharge in patients stratified according to bleeding risk scores. Our data are further corroborated by Colombo et al who recently reported a higher risk of haemorrhagic stroke in HM3 patients managed with aspirin vs. patients on oral anticoagulation alone (86% vs. 57%), and a comparable incidence of ischaemic stroke in the two groups, meaning that aspirin might exacerbate the pathophysiology of bleeding disorders in HM3 patients, and that anticoagulation alone is effective and safe in preventing these phenomena. In this perspective, the value of low‐intensity anticoagulation (INR target 1.5–1.9) and aspirin therapy, as proposed by Netuka et al in the Minimal AnticoaGulation EvaluatioN To aUgment heMocompatibility (MAGENTUM 1) study, appears less attractive to reduce HM3 HRAEs.…”
Section: Preoperative Characteristics Of Patients Discharged With Andsupporting
confidence: 89%
See 2 more Smart Citations
“…This study shows safety and efficacy of an aspirin‐free antithrombotic regimen in reducing HRAEs in patients implanted with the HM3, and further expands the results by Lim et al , suggesting the potential benefit of primary warfarin monotherapy after discharge in patients stratified according to bleeding risk scores. Our data are further corroborated by Colombo et al who recently reported a higher risk of haemorrhagic stroke in HM3 patients managed with aspirin vs. patients on oral anticoagulation alone (86% vs. 57%), and a comparable incidence of ischaemic stroke in the two groups, meaning that aspirin might exacerbate the pathophysiology of bleeding disorders in HM3 patients, and that anticoagulation alone is effective and safe in preventing these phenomena. In this perspective, the value of low‐intensity anticoagulation (INR target 1.5–1.9) and aspirin therapy, as proposed by Netuka et al in the Minimal AnticoaGulation EvaluatioN To aUgment heMocompatibility (MAGENTUM 1) study, appears less attractive to reduce HM3 HRAEs.…”
Section: Preoperative Characteristics Of Patients Discharged With Andsupporting
confidence: 89%
“…Indeed, this strategy did not completely blunt the incidence of recurrent bleeding episodes . Furthermore, according to Colombo et al , we cannot exclude that reduced anticoagulation levels might portend a higher risk of ischaemic stroke.…”
Section: Preoperative Characteristics Of Patients Discharged With Andmentioning
confidence: 78%
See 1 more Smart Citation
“…Early survival after implantation is satisfactory, although at times at the expense of device‐related complications 1‐3 . Significant improvement of the hardware and implantation procedure has greatly reduced device failure 4‐6 . Neurologic adverse events continue to represent a significant challenge to the long‐term outcomes after MCS device placement 2,5,7‐11 …”
Section: Introductionmentioning
confidence: 99%
“…The clinical significance of these features is a decreased risk of haemocompatibility‐related SAEs compared with its predecessor, the HMII (which consisted of an axial continuous‐flow pump with mechanical bearings), and, theoretically, a lower risk of thromboembolism than with other devices operating on similar principles. Compared with the HMII, the HM3 was associated with fewer haemocompatibility‐related events during short‐term (6 months) follow‐up and a marked reduction in the incidence of stroke in the long‐term follow‐up phase (up to 2 years) of the MOMENTUM 3 trial (odds ratio 0.23, 95% confidence interval 0.08–0.63; P = 0.01) . Implantation of an HM3 pump was the only independent predictor of a lower incidence of stroke in MOMENTUM 3, a finding of significance when it is considered that the occurrence of stroke of any type or of any functional severity was predictive of poor 2‐year clinical outcome.…”
Section: Discussionmentioning
confidence: 93%